1999
DOI: 10.1080/001401399184857
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cognitive processes of experienced air traffic controllers

Abstract: A model of the cognitive activities of experienced air traffic controllers is presented as an example of the challenging theoretical task to model mental processes in a dynamic task environment. Owing to the continuous changes in the task environment and the demand for the temporal co-ordination of activities in air traffic control, the model pays special attention to the mental representation of the situation. This unit of the model plays a salient role in maintaining situational awareness, in anticipating fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…These models do not yet include a conflict detection component. Other models of air traffic control performance do include a conflict detection component (Corker et al, 2000;Leiden, Kopardekar, & Green, 2003;Niessen, Eyferth, & Bierwagen, 1999) but do not necessarily describe the cognitive processes that are involved. Fuzzy SDT (Parasuraman, Masalonis, & Hancock, 2000) has been applied to conflict detection, but it is a measurement model rather than a process model.…”
Section: Introductionmentioning
confidence: 98%
“…These models do not yet include a conflict detection component. Other models of air traffic control performance do include a conflict detection component (Corker et al, 2000;Leiden, Kopardekar, & Green, 2003;Niessen, Eyferth, & Bierwagen, 1999) but do not necessarily describe the cognitive processes that are involved. Fuzzy SDT (Parasuraman, Masalonis, & Hancock, 2000) has been applied to conflict detection, but it is a measurement model rather than a process model.…”
Section: Introductionmentioning
confidence: 98%
“…Information Reduction applies in situations in which tasks contain both relevant and irrelevant information, and denotes a change from a strategy that is based on exhaustive processing of all elements of a task to a strategy that skips the irrelevant task elements. Behavior in line with the notion of Information Reduction has been described in educational psychology (Gaeth & Shanteau, 1984), sports (Helsen & Pauwels, 1993), car-driving (Underwood, Crundall, & Chapman, 2002), expert air traffi c controllers (Niessen, Eyferth & Bierwagen, 1999), and in many other domains.…”
mentioning
confidence: 97%
“…Vingelis, Schaeffer, Stringer, Gromelski, and Ahmed (1990) further suggested that controllers consider aircraft in pairs (i.e., conflicting pairs and others). Pairs of aircraft can be further classified as focal, of immediate value, or extrafocal, not of immediate value (Niessen, Eyferth, & Bierwagen, 1999). Leplat and Bisseret found that controllers made such determinations by comparing six specific attributes of aircraft pairs.…”
mentioning
confidence: 99%